1997
DOI: 10.1177/019394599701900403
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and Addiction Experiences of African American Women

Abstract: Substance abuse affects African American women at an increasingly alarming rate. The interaction of substance abuse and traumatic events requires exploration. For many African American women, early life trauma plays a critical role in how and when they fall victim to the ravages of substance abuse. This article about a phenomenological study of 15 African American women uses intense narratives to disclose experiences of incest, rape, abuse, and other horrors that led to drug and alcohol use to extinguish pain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 30 publications
0
46
0
1
Order By: Relevance
“…Prevalence of sexual revictimization (e.g., women abused in childhood and adulthood) is high, with women who have experienced CSA at higher risk for adult victimization than those without a history of CSA (Classen, Palesh, & Aggarwal, 2005;Messman-Moore & Brown, 2004;MessmanMoore & Long, 2000). Past research has also shown that revictimized women are also at increased risk to use drugs and alcohol (Filipas & Ullman, 2006;Messman-Moore & Long, 2003;Siegel & Williams, 2003). One theory as to why revictimized women abuse drugs and alcohol is that it is a method of coping with past abuse (Filipas & Ullman, 2006;Hall, 2000).…”
Section: Problem Drinking/illicit Drug Use and Sexual Assaultmentioning
confidence: 99%
See 2 more Smart Citations
“…Prevalence of sexual revictimization (e.g., women abused in childhood and adulthood) is high, with women who have experienced CSA at higher risk for adult victimization than those without a history of CSA (Classen, Palesh, & Aggarwal, 2005;Messman-Moore & Brown, 2004;MessmanMoore & Long, 2000). Past research has also shown that revictimized women are also at increased risk to use drugs and alcohol (Filipas & Ullman, 2006;Messman-Moore & Long, 2003;Siegel & Williams, 2003). One theory as to why revictimized women abuse drugs and alcohol is that it is a method of coping with past abuse (Filipas & Ullman, 2006;Hall, 2000).…”
Section: Problem Drinking/illicit Drug Use and Sexual Assaultmentioning
confidence: 99%
“…Past research has also shown that revictimized women are also at increased risk to use drugs and alcohol (Filipas & Ullman, 2006;Messman-Moore & Long, 2003;Siegel & Williams, 2003). One theory as to why revictimized women abuse drugs and alcohol is that it is a method of coping with past abuse (Filipas & Ullman, 2006;Hall, 2000). In Filipas and Ullman's (2006) study of 577 students, sexually revictimized women were more likely to use drugs and alcohol to cope than nonrevictimized sexual assault victims.…”
Section: Problem Drinking/illicit Drug Use and Sexual Assaultmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, her history of sexual assault is a contextual factor-one that is of significance for her. These factors are linked to heightened risk for traumatic exposure (Davis, 1997).…”
mentioning
confidence: 99%
“…In her detailed study of African American women's experiences of trauma and addiction, R. E. Davis (1997) raised the following key points:…”
mentioning
confidence: 99%